Accelerometer-measured sedentary behavior and risk of functional disability in older Japanese adults: a 9-year prospective cohort study - Tao Chen; Sanmei Chen; Takanori Honda; Hiro Kishimoto; Yu Nofuji; Kenji Narazaki (BMC, 2023)
Abstract Background The associations of sedentary time and patterns with functional disability among older adults remain unclear, and few studies have accounted for the co-dependency of sedentary behavior and physical activities when modeling sedentary behavior with risk of functional disability. We aimed to examine the associations between sedentary time and patterns and risk of incident functional disability, and assess whether replacing sedentary time with light physical activity (LPA) or moderate-to-vigorous intensity physical activity (MVPA) is associated with reduced risk of functional disability in community-dwelling older adults. Methods A total of 1,687 Japanese adults aged ≥ 65 years without functional disability at baseline were prospectively followed-up for 9 years (2011-2020). Functional disability was ascertained using the national database of Japan's Long-term Care Insurance System. Sedentary time and patterns, LPA, and MVPA were measured using a tri-axial accelerometer secured to participants' waists. Results During follow-up, 466 participants developed functional disability. Compared with the lowest quartile of total sedentary time, the multivariable-adjusted hazard ratios (95% confidence intervals) of functional disability for the second, third, and top quartiles were 1.21 (0.91‒1.62), 1.45 (1.10‒1.92), and 1.40 (1.05‒1.88) (p for trend = 0.01). After further adjusting for MVPA, total sedentary time was no longer significantly associated with the risk of functional disability (p for trend = 0.41). Replacing 10 min/day of sedentary time with the same amount of MVPA (but not LPA) was significantly associated with a 12% reduced risk of functional disability (hazard ratio [95% confidence interval]: 0.88 [0.84‒0.92]). No significant association was observed between sedentary bout length and functional disability. Conclusion Higher levels of total sedentary time were associated with an increased risk of incident functional disability. However, this association was not independent of MVPA. Replacing sedentary time with MVPA, but not LPA, was associated with reduced risk of functional disability in older adults.